1999
DOI: 10.1002/(sici)1096-9071(199905)58:1<26::aid-jmv4>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of successful outcome in a randomised controlled trial of the long-term efficacy of interferon alpha treatment for chronic hepatitis C

Abstract: To evaluate the efficacy of a 12-month course of recombinant interferon alpha (IFN-alpha2b), and to assess predictive factors of successful response to IFN therapy in chronic active hepatitis C (HCV CAH), 242 patients with histologically proven HCV CAH were assigned randomly to two groups, one treated with IFN-alpha2b (3 MU three times weekly, intramuscularly), the other untreated. To determine the efficacy of IFN-alpha2b 12 months after therapy, a second liver biopsy was carried out on 100 treated patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
1
7
1
Order By: Relevance
“…The most likely explanation is that genotype dominated the outcome. Many previous studies reported that lower serum HCV RNA levels at entry and milder disease correlated with an increase in the probability of response to IFN [13–26]. Since the ETR of African Americans is lower but entry serum HCV RNA is not statistically different from Caucasians, the two factors could combine to explain the observation that entry serum HCV RNA was not a predictive factor in our urban clinic population.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The most likely explanation is that genotype dominated the outcome. Many previous studies reported that lower serum HCV RNA levels at entry and milder disease correlated with an increase in the probability of response to IFN [13–26]. Since the ETR of African Americans is lower but entry serum HCV RNA is not statistically different from Caucasians, the two factors could combine to explain the observation that entry serum HCV RNA was not a predictive factor in our urban clinic population.…”
Section: Discussionmentioning
confidence: 65%
“…Serum HCV RNA as measured by PCR methodology is currently used for determining response to therapeutic interventions in patients with CHC. This is based on the concept that elimination of the virus rather than normalization of ALT is the initial goal of therapy [9–14]. Since IFN‐α2b monotherapy can cause unpleasant side‐effects, is expensive, and is associated with a low sustained response rate (SR; 5–10%), defining host or viral parameters that would allow identification of responders or nonresponders prior to the initiation of therapy is a secondary goal of most clinical trials [13–26].…”
Section: Introductionmentioning
confidence: 99%
“…Organ transplant recipient It would appear that younger patients respond better to anti-viral therapy than older patients [39]. Whether this is a function of the relative potency of the immune repertoire at …”
Section: Factors That Impact On Anti-viral Therapy Outcomementioning
confidence: 99%
“…[49][50][51] The impact of genotype on posttransplant outcome is less clear. Studies differ in terms of diagnostic criteria for severe recurrence, length of follow-up, and end points.…”
Section: Viral Genotypementioning
confidence: 99%